Teritorialitas Ruang Publik dan Semi Publik pada Rumah Susun di Kelurahan Kaligawe Kota Semarang - Isna Fitriantika (Jurnal Talenta Sipil, 2026)
The need for decent housing continues to increase, while the availability of residential land is becoming increasingly limited. Apartment buildings are one solution to this problem, including the apartment building in Kaligawe Village, Semarang City, which consists of seven twin blocks. Preliminary studies show that there are various types of spaces in these apartment buildings, namely public, semi-public, and private spaces. However, over time, public and semi-public spaces have been converted into private spaces through territorial marking, both physically and symbolically, such as placing private benches on the terraces of residences. This study aims to identify and understand the forms, causes, effects, signs, and meanings of territoriality in public and semi-public spaces in these apartment buildings. The method used is qualitative descriptive with Irwin Altman's territorial theory and behavioral mapping observation techniques. The results of the study show that there is permanent and temporary territoriality, both conscious and unconscious, as a form of adaptation by residents to spatial limitations. Territoriality on residential terraces, emergency stairwells, and multipurpose hallways are considered primary territories, while halls and connecting bridges are secondary territories, and fields, parking lots, and stairwells are public territories. In conclusion, territoriality in the Kaligawe apartment complex reflects the residents' need to assert their identity, ownership, and comfort in a dense vertical environment.